Compression sutures combined with intracameral air injection versus thermokeratoplasty for acute corneal hydrops: a prospective-randomised trial. Issue 12 (3rd October 2020) - Zhao, Zelin; Wu, Siteng; Ren, Weina; Zheng, Qinxiang; Ye, Cong; Kim, Andy D.; Jhanji, Vishal; Wang, Michael T. M.; Chen, Wei
Abstract : Aims: To compare the efficacy of compression sutures combined with intracameral air injection (CSAI) and thermokeratoplasty (TKP) for the management of acute corneal hydrops in keratoconus. Methods: In this multi-centre randomised clinical trial, 20 patients with keratoconus (20 eyes) with acute corneal hydrops were enrolled and randomised to receive either CSAI or TKP and followed-up for a period of 6 months. Results: There were no significant differences in patient demographics, severity of corneal hydrops and preoperative duration of symptoms between the two groups. In both groups, corneal oedema resolved within 2 weeks. The maximum thickness of the corneal scars following CSAI and TKP was not significantly different. Best spectacle-corrected visual acuity was superior in the CSAI group at 6-month follow-up (CSAI vs TKP, 0.52 (0.37, 0.85) vs 0.96 (0.70, 1.34) LogMAR, p=0.042). CSAI resulted in greater corneal endothelial cell density (CSAI vs TKP, 2677.8±326.7 vs 1955.3±298.1 cells/mm 2, p<0.001) and flatter corneal curvature (CSAI vs TKP: mean keratometry value, 52.13±4.92 vs 63.51±5.83D, p<0.001; maximum keratometry value, 65.21±7.42 vs 77.13±12.01D, p=0.016) at the 6-month follow-up. Conclusion: Although both CSAI and TKP resulted in resolution of acute corneal hydrops in keratoconus, CSAI was associated with superior clinical outcomes in this study. Chinese Clinical trial registration number: ChiCTR-IOR-17013764